Environmental Risk Considerations in the Development of Solid Waste Facility: Case Study Rawa Kucing Solid Waste Facility, Tangerang City - Lingkan Claudia Poluakan; Pramiati Purwaningrum; Dwi Indrawati (Universitas Trisakti, 2018)
Tangerang City is one of the cities in Banten Province. The dense population causes an increase in the volume of waste, so an adequate Solid Waste Facility (SWF) is needed. Solid Waste Facility is the place to process and return the waste to the environment. Rawa Kucing SWF is one that serves Tangerang City with an area of 37.7 hectares, divided into four landfill zones and landfill support facilities. With the remaining land that can be used to build a new landfill, it is necessary to conduct a study on the feasibility of Rawa Kucing SWF if it is still feasible as seen by the environmental conditions or not. In the Regulation of the Minister of Public Works Number 3 of 2013, there is a land suitability assessment for taking decision of SWF whether it is to be rehabilitated or should be closed known as the Integrated Risk Based Approach (IRBA). The result of the environmental risk index assessment based on IRBA is 599.03, which means that mean Rawa Kucing SWF is included in moderate hazard category. The recommended action in this category is that the TPA is continued and rehabilitated into gradually controlled landfill. Currently, the Rawa Kucing SWF has applied controlled landfill method, so the effort to develop the landfill method into sanitary landfill method can be done gradually to reduce adverse impact to the environment. Technology such as Waste-to-Energy (WtE) Plants can also be considered to reduce the waste load entering the landfill.